Implementing the Anti-Human Trafficking Policy in Nigeria: Trials and Tribulations - Usman, Usman Mikail; Ariffin, Raja Noriza Raja; Othman, Azmah Binti Haji (The journal of contemporary issues in business and government, 2021)
This study analyses the implementation of the National Agency for the Prohibition of Trafficking in Persons (NAPTIP) Policy in Nigeria. Nigeria was selected due to the continuing increase in human trafficking and the subsequent challenges resulting from this phenomenon. The government has taken critical measures to fight human traffickers particularly by using the United Nations protection, prevention, and prosecution approach. However, the method seems to have failed in reducing the menace and the lack of coordination and communication amongst relevant organisations handling human trafficking seems to have been the main cause that have hampered the implementation of the policy. The research uses qualitative inquiry of one-on-one interviews with informants from the NAPTIP, academics and non-governmental organisations involved in combating human trafficking. The findings show that there is a need to have a well-defined task and enhanced coordination and communication amongst the relevant anti-trafficking agencies.